A New Anthropophilic Species of Simulium (Trichodagmia) (Diptera: Simuliidae) From Amazonia: Morphology, Chromosomes, and DNA Sequences. Issue 1 (2nd October 2017) - Nascimento, Jeane Marcelle Cavalcante Do; Hamada, Neusa; Andrade-Souza, Vanderly; Adler, Peter H
Abstract: The black fly Simulium ( Trichodagmia ) hirtipupa Lutz (Diptera: Simuliidae) is widely distributed in southern Brazil, with one report from Amapá state in the northern region of Brazilian Amazonia. Morphological comparison of northern and southern populations revealed differences in all life stages, corroborated by chromosomal and molecular analyses, and indicated that the population previously identified as S. hirtipupa from Amapá state represents an undescribed species. This new species is described based on all life stages above the egg, and its chromosomal and molecular divergence from S. hirtipupa is highlighted. Simulium criniferum n. sp. can be diagnosed by the deeply concave male ventral plate with a prominent median projection bearing a ventral keel; female anal lobe in lateral view with a broadly rounded, distal membranous area about as long as wide; pupa with a boot-shaped cocoon bearing a minutely bubbled surface, cephalic plate and thorax with abundant hair-like tubercles, and gill of 12 translucent filaments with darkly sclerotized, acuminate tips; and larva with the body cuticle bearing spiniform setae, abdomen truncated posteriorly, and gill histoblast in situ with the filament tips directed ventrally. Chromosomally, the new species has five unique fixed inversions and uniquely shares three additional fixed inversions with its nearest relative, S. hirtipupa . Partial COI sequences indicate a genetic distance of ~9% between the new species and S. hirtipupa . Females of the new species are anthropophilic.